The Effect of Volume and Surface Area Ratio of Medium on Bacterial Cellulose Production at Different Fermentation Times by Gluconacetobacter sp. SAL53 - Puspita, Chaerina Wardiani; Sarkono; Kusuma, A.A. Ngurah Nara; Zana, M. Zannatun Naeem (Indonesian Journal of Tropical Biology, 2026)
Bacterial cellulose is an extracellular polysaccharide synthesized by several bacterial genera, including Gluconacetobacter sp. SAL53, and has broad potential applications in biotechnology, food, and biomedical industries. Since this bacterium requires aerobic conditions, oxygen availability becomes a key factor influencing cellulose biosynthesis. The surface area of the fermentation medium affects oxygen transfer, while fermentation time determines the duration of bacterial metabolic activity and cellulose accumulation. This study aimed to evaluate the effects of different fermentation medium surface areas and fermentation durations on BC production. The experiment used four container diameters corresponding to surface areas of 78.5, 176.6, 314.0, and 490.6 cm², combined with fermentation periods of 5, 10, and 15 days. The results demonstrated that both surface area and fermentation time significantly influenced BC yield. Increased surface area and prolonged fermentation led to higher BC thickness, wet weight, and dry weight. The highest production was obtained under treatment P4W3, with a surface area of 490.6 cm² and a fermentation period of 15 days, yielding a thickness of 1.33 cm, wet weight of 415.5 g, and dry weight of 4.85 g. This condition was also characterized by a final pH of 3.89, the lowest reducing sugar content (5.22%), and the lowest remaining volume (350 mL), indicating optimal bacterial metabolism. These findings confirm that fermentation surface area and duration are critical factors for optimizing BC production.